The Economic Inefficiency of Travel Passes Under Crowding Externalities and Endogenous Capacity. (1st January 2018) - Hörcher, Daniel; Graham, Daniel; Anderson, Richard
Travel passes provide benefits for frequent travellers as well as financially constrained public transport operators, who thus can price discriminate and generate revenues efficiently. This paper argues that the presence of crowding externalities may neutralise the welfare benefits of travel pass provision, because a zero marginal fare after an initial entry payment leads to inevitable overconsumption. Therefore, only severely under-subsidised welfare maximising operators should supply season tickets. We show that the ignorance of crowding externalities and a demand maximising (political) objective may be two potential explanations why travel passes are still widely used in public transport.